Penyuluhan Tentang Pentingnya Mematuhi Protokol Kesehatan untuk Menjaga Stabilitas Kegiatan Mengaji di Pondok Pesantren Darusalam Lereng Kelud Kec.Kepung Kab. Kediri - Era Islamiyati; Maryadi (LP3M IAIFA Kediri, 2021)
Corona Virus Disease 2019 or COVID-19 is a new type of disese caused by infection with the Severe Acute Syndrom Coronavirus-2 (SARCOV-2) or known as the novel coronavirus (2019-nCoV). From its initial appereance at the end of 2019 until now this disease has infected 4,789,205 people and caused the death of 318,789 people worldwide. To start the activity, learn fist so that students can easly make handsanitizer and make their own at home, the next activity is to distribute masks to student and give the impression that when they wan to leave the house they must wear masks and comply with health protocols because maintaining health is also very important. In this study the authors used the PAR (Participation Resarch Action) research method. The PAR method is a process by which communities try to study the problem scientifically in order to guide, improve, evaluate the decisions of their action. Research methods that have been commonoly conducted among academics and researchers in the community, can actually be a challenge and a threat to a community. Participatory action research is research that is characterized by the active involvement of the target group. Action research places the communty who is te target group as a subject in the activity process and not as an abject. In PAR, the researcher places himself as an insider not as un outsider or between the subject and object. Reseachers generally have a tendency to build a caustic approach. PAR is a (research) with action (action) that is carried out in a participatiry manner in order to improve aspect of people’s lives.